Development of resue antiemetic guidelines for the management of chemotherapy induced nausea and vomiting in paediatric patients at the RHSC, Edinburgh. Issue 6 (1st February 2011) - Zingel, J; Ferguson, J; Kinnear, M; Johnson, J; Hudson, S
Abstract : Objective: To review and update the existing local antiemetic guidelines at the Royal Hospital for Sick Children (RHSC) Haematology/Oncology Department, Edinburgh in line with current best practice and produce evidence based rescue antiemetic guidelines for the management of chemotherapy-induced nausea and vomiting (CINV) in paediatric patients with haematological/oncological malignancies. Methods: An extensive literature search on antiemetics and the management of CINV in paediatrics was undertaken and current local antiemetic guidelines from the Royal Hospital for Sick Children, Edinburgh (RHSCE) and three other UK paediatric Haematology/Oncology centres were reviewed. Semistructured questionnaires were designed and issued to doctors, pharmacist and nurses with expertise in paediatric haematology/oncology practicing at the RHSCE to obtain their opinions on the local antiemetic guidelines and the information regarding their practice in management of breakthrough/delayed and refractory CINV in paediatric patients. A multidisciplinary team discussion took place to approve the draft guidelines. Results: The revised guidelines now include: updated prophylactic sections for acute and delayed CINV and a rescue antiemetic therapy section for breakthrough and refractory emesis for all CINV phases, treatment flow charts, drug information table for drugs used in the management of CINV and chemotherapy regime specific antiemetic guidelines. In addition, these revised guidelines 'step up' the antiemetic cover provided to children receiving highly emetogenic chemotherapy which have, in the past, proven difficult to manage. Conclusion: The revised antiemetic guidelines provide a decision support system for clinicians and other healthcare professionals in applying evidence-based antiemetic treatment strategies for the management of CINV into their practices and support the use of appropriate care to each patient. Anecdotally we believe these guidelines have improved our practice however, a formal audit requires to be undertaken to validate this belief.